Detection of various virulence factors in high level aminoglycoside resistance and vancomycin resistant enterococci isolates of uropathogenic Enterococci - Naruka, Harshad Singh; Chand, Anita E.; Chauhan, Pradhuman Singh; Mukhtar, Danish (International Journal of Research in Medical Sciences, 2019)
Background: Enterococci are common commensal organism of enteric tract and act as opportunistic pathogen and may cause infection in community as well as in hospitalised individuals. In present study association of several types of virulence factors like haemolysin, gelatinase and biofilm formation have been studied among HLAR and Vancomycin resistant Enterococci (VRE) isolates of enterococci among UTI patients. Methods: The samples were collected from all hospitalized and OPD patients of MBS Hospital, JK Lone Hospital and NMC Hospital. Government Medical College, Kota, Rajasthan, India. A total of 360 isolates of enterococcus were collected during the period of 2 years from April 2016 to April 2018 in microbiology laboratory, Department of Microbiology, Government Medical College, Kota, Rajasthan, India. All virulence factors were detected by phenotypic methods and MIC values were detected for high level gentamicin and vancomycin. Results: Among all enterococcal isolates most common factor was biofilm production 191 (53.05%) followed by haemolysin 131 (36.38%) and gelatinase production 72 (20%). Total resistant (MIC> 500 µg/ml) isolates for gentamicin was 194 (89.4%). In agar dilution 14 (11.2%) isolates were found sensitive, 61 (48.8%) isolates were found intermediate and 50 (40%) isolates were found to be resistant for vancomycin. HLAR and VRE was maximum associated with haemolysin + bio-film followed by gelatinase+biofilm, haemolysin+gelatinase+bio- film and least with haemolysin + gelatinase. Conclusions: In present study enterococcus show significant production of biofilm and other virulence factors. With production of biofilm they become more resistant to routinely used concentration of antibiotics posing threat for treatment failure. A continuous monitoring is needed particularly for resistance to aminoglycoside and vancomycin to stop their institutional spread. Judicial use of antibiotics should be encouraged both in community as well as in institutions.